Assessment of Antibacterial Activity and Minimal Inhibitory Concentration of Leaf Extract of Morinda Citrifolia Against Enterococcus Feacalis- An Invitro Study (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: bacteria; biofilm; endodontics; morinda citrifolia leaves; root canal